Financial toxicity and firearm injury: exploring financial needs of participants in a hospital-based violence intervention program - Ana M Reyes; Carlene McKenzie; Meghan Scott; Christopher R Haggerty; Julie Y Valenzuela (Trauma Surgery & Acute Care Open)
Background Financial toxicity refers to financial hardship experienced because of illness or injury. Poverty is a known driver of community violence, but financial toxicity has not been studied in firearm violence survivors. The objective of our study was to explore the financial needs of firearm violence survivors enrolled in a hospital-based violence intervention program (HVIP). We hypothesized that survivors would report numerous financial needs.Methods This was a mixed-methods, retrospective study of firearm violence survivors enrolled in the Miami-Dade County HVIP from 2022 to 2023. Patients were eligible for enrollment if they were injured in shooting incidents that occurred in Miami-Dade police districts with high rates of group violence or gang-related violence. Social worker intake and longitudinal case records were reviewed. A qualitative thematic analysis of social worker notes was performed. Quantitative data were analyzed with descriptive statistics and χ2 tests for association.Results 103 patients were enrolled in the program. The median age was 27 years. The majority of patients were black (82.5%) and male (83.5%). More patients were insured (59.2%) than uninsured (40.8%). Thematic analysis revealed 10 distinct financial needs, including assistance with victim crime compensation (75.7% of patients), medical bills (35.0%), wage loss (22.3%), insurance applications (14.6%), burial (13.6%), and emergency relocation (12.6%). Overall, financial needs were identified for 94 (91.3%) patients: 91 (88.3%) at initial program intake and 3 additional patients (2.9%) during longitudinal case management.Conclusions Survivors of firearm violence experience financial challenges after injury. Thus, financial support and assessment for financial toxicity should be included in firearm violence survivorship programs. Future investigations should use validated measures to study the financial toxicity of firearm violence survivors longitudinally.